2014
DOI: 10.1007/s10006-014-0451-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary parapharyngeal tumours: a review of 21 cases

Abstract: The number of perioperative complications encountered in this series confirms the difficulty of performing surgery in this complex area, even in benign cases. The chances of avoiding vascular damage and saving the trunks or most of the nerve fibres involved depend not only on the skill and experience of the surgeon but also on the anatomy of the lesion, the type of connection between the tumour and the nerve from which it originates and the distribution of neural fibres in or around the tumour mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Enhanced CT is useful for analysis of tumor location and to preoperatively establish a method of approach for surgery (10). Three dimensional-CT angiography is indicated when the tumor is suspected to be a carotid body tumor from its location, in order to evaluate its vascularity and confirm the diagnosis (21).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced CT is useful for analysis of tumor location and to preoperatively establish a method of approach for surgery (10). Three dimensional-CT angiography is indicated when the tumor is suspected to be a carotid body tumor from its location, in order to evaluate its vascularity and confirm the diagnosis (21).…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that they could not perform FNAB in post-styloid area tumors because of major risks and nondiagnostic samples. 11 In a study performed by Arnoson et al on 27 patients whose benign-malignant PPS tumors were confirmed with both surgery and imaging techniques, specific diagnosis were only obtained from 36% of all FNAB samples. In this study, the reliability of FNAB was reported as %92 in the diagnosis of positive and negative malignancy, and nondiagnostic sample rate was reported as %31.…”
Section: Discussionmentioning
confidence: 99%
“…Parapharyngeal space (PPS) tumors are rare lesions that comprise less than 0.5% of head and neck masses [42]. The majority of the lesions, 66.4% up to 87.3% of the cases, are benign and 18% are malignant [42,43] (Table 3). The PPS is a complex space located in the suprahyoid neck resembling a pyramid with the base formed by the skull base and the apex pointing to the greater cornu of the hyoid bone, mainly divided pre-and poststyloid space [44].…”
Section: Parapharyngeal Cystsmentioning
confidence: 99%